2005
DOI: 10.1111/j.1469-8137.2005.01456.x
|View full text |Cite
|
Sign up to set email alerts
|

Canopy and environmental control of root dynamics in a long‐term study of Concord grape

Abstract: Summary• Below-ground carbon allocation represents a substantial fraction of net photosynthesis in plants, yet timing of below-ground allocation and endogenous and exogenous factors controlling it are poorly understood.• Minirhizotron techniques were used to examine root populations of Vitis labruscana Bailey cv. Concord under two levels of dormant-season canopy removal and irrigation. Root production, pigmentation, death and disappearance to a depth of 110 cm were determined over two wet and two dry years (19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
116
1
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(130 citation statements)
references
References 34 publications
8
116
1
5
Order By: Relevance
“…data) presented the results from this study that had clearly demonstrated the roots to undergo large morphological and structural changes to ensure desirable distribution when adapting to terminal drought as described in wheat previously (Sharp and Davies 1985). These changes were (i) early reduction or check in root prolificacy in surface soils most likely due to the early death of ultimate branches, (ii) greater prolificacy of roots in soil depths below 30 cm, and to a much greater extent below 75 cm, thereby increasing the proportion of deeper soil roots (Lafitte et al 2001;Mishra et al 2001;Comas et al 2005;Benjamin and Nielsen 2006;Guswa 2008;Henry et al 2011), (iii) reduction in overall root biomass (Robertson et al 1980;Sánchez-Blanco et al 2002;dos Santos et al 2007;Navarro et al 2009;Álvarez et al 2009, 2011, (iv) reduction in root thickness, thereby increase in root length within the available root biomass, and to explore more volume of soil (Bañon et al 2003;Koike et al 2003;Kulkarni and Deshpande 2007;Chylinski et al 2007;Franco et al 2008;De Sousa and Lima 2010;Álvarez et al 2011;Wasson et al 2012;Bandyopadhyay 2014) and (v) early senescence of root system matching the shoot system senescence with no relevance to soil water availability. Similar pattern of RLD distribution was also observed in several legumes and cereal species such as field pea, rice, canola, cowpea, sunflower and sorghum (Liu et al 2011;Gowda et al 2012;Cutforth et al 2013;Moroke et al 2005).…”
Section: Adaptation To Terminal Droughtmentioning
confidence: 85%
“…data) presented the results from this study that had clearly demonstrated the roots to undergo large morphological and structural changes to ensure desirable distribution when adapting to terminal drought as described in wheat previously (Sharp and Davies 1985). These changes were (i) early reduction or check in root prolificacy in surface soils most likely due to the early death of ultimate branches, (ii) greater prolificacy of roots in soil depths below 30 cm, and to a much greater extent below 75 cm, thereby increasing the proportion of deeper soil roots (Lafitte et al 2001;Mishra et al 2001;Comas et al 2005;Benjamin and Nielsen 2006;Guswa 2008;Henry et al 2011), (iii) reduction in overall root biomass (Robertson et al 1980;Sánchez-Blanco et al 2002;dos Santos et al 2007;Navarro et al 2009;Álvarez et al 2009, 2011, (iv) reduction in root thickness, thereby increase in root length within the available root biomass, and to explore more volume of soil (Bañon et al 2003;Koike et al 2003;Kulkarni and Deshpande 2007;Chylinski et al 2007;Franco et al 2008;De Sousa and Lima 2010;Álvarez et al 2011;Wasson et al 2012;Bandyopadhyay 2014) and (v) early senescence of root system matching the shoot system senescence with no relevance to soil water availability. Similar pattern of RLD distribution was also observed in several legumes and cereal species such as field pea, rice, canola, cowpea, sunflower and sorghum (Liu et al 2011;Gowda et al 2012;Cutforth et al 2013;Moroke et al 2005).…”
Section: Adaptation To Terminal Droughtmentioning
confidence: 85%
“…In response to a very dry year where switchgrass received 40% less precipitation compared to the 30-year average, both ecotypes lost a large proportion of root biomass. Root system responses to water availability and dry soil are often specific to the degree and can be opposing depending on the level of dryness (Comas et al, 2005). For example, small shortfalls in water availability can increase root production in plants, while extremely dry soil will limit root production; likewise, some species, even with succulent fine roots, retain these roots under moderate drought but may not under extreme conditions (Comas et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Root system responses to water availability and dry soil are often specific to the degree and can be opposing depending on the level of dryness (Comas et al, 2005). For example, small shortfalls in water availability can increase root production in plants, while extremely dry soil will limit root production; likewise, some species, even with succulent fine roots, retain these roots under moderate drought but may not under extreme conditions (Comas et al, 2005). Garten et al (2010) showed an increase in root production during the latter part of the growing season in rainfed switchgrass in the southeast US.…”
Section: Discussionmentioning
confidence: 99%
“…Shoot growth may be more strongly affected by water limitations than its reproductive growth, but also, roots development can be limited. These limitations could appear especially in warm, dry climates or under water scarcity conditions, mainly when reproductive demands for carbon were at its highest and physical conditions limiting their development during the cycle [8,9].Therefore, an adequate balance among crop load, training -trellising system and water management should be required in warm climates as a key point in order to assess the expected quality for grapes and wine.The main objective of the present work was to examine the effects of three different training systems on water consumption (relations between soil-plant) and also, their effect on yield and grape quality under Mediterranean warm climate conditions. …”
mentioning
confidence: 99%
“…Shoot growth may be more strongly affected by water limitations than its reproductive growth, but also, roots development can be limited. These limitations could appear especially in warm, dry climates or under water scarcity conditions, mainly when reproductive demands for carbon were at its highest and physical conditions limiting their development during the cycle [8,9].…”
mentioning
confidence: 99%